2011
DOI: 10.4061/2011/939068
|View full text |Cite
|
Sign up to set email alerts
|

Asp295 Stabilizes the Active-Site Loop Structure of Pyruvate Dehydrogenase, Facilitating Phosphorylation of Ser292 by Pyruvate Dehydrogenase-Kinase

Abstract: We have developed an in vitro system for detailed analysis of reversible phosphorylation of the plant mitochondrial pyruvate dehydrogenase complex, comprising recombinant Arabidopsis thalianaα2β2-heterotetrameric pyruvate dehydrogenase (E1) plus A. thaliana E1-kinase (AtPDK). Upon addition of MgATP, Ser292, which is located within the active-site loop structure of E1α, is phosphorylated. In addition to Ser292, Asp295 and Gly297 are highly conserved in the E1α active-site loop sequences. Mutation of Asp295 to A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Previous studies of the D295N change using peptide substrates with the mammalian PDK showed substantially reduced phosphorylation of S 292 , and it was proposed that Asp 295 is involved with PDK binding (Mullinax et al, 1985 ). The results of Mullinax et al ( 1985 ) were recently verified by Hirani et al ( 2011 ) using recombinant A. thaliana PDC-E1 and PDK. The D295N, D295A, and D295L site-directed mutants all had greatly reduced phosphorylation of E1α.…”
Section: Resultsmentioning
confidence: 65%
See 4 more Smart Citations
“…Previous studies of the D295N change using peptide substrates with the mammalian PDK showed substantially reduced phosphorylation of S 292 , and it was proposed that Asp 295 is involved with PDK binding (Mullinax et al, 1985 ). The results of Mullinax et al ( 1985 ) were recently verified by Hirani et al ( 2011 ) using recombinant A. thaliana PDC-E1 and PDK. The D295N, D295A, and D295L site-directed mutants all had greatly reduced phosphorylation of E1α.…”
Section: Resultsmentioning
confidence: 65%
“…During the genome-sequencing era it has been established that the position of Ser 292 and the sequences of the flanking amino acids are highly conserved in mtPDC E1α sequences. When directly studied, it has been verified that Ser 292 was phosphorylated by the intrinsic PDK (e.g., Bykova et al, 2003 ; Hirani et al, 2011 ).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations